2022
DOI: 10.1038/s41598-022-11555-4
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer type and humic acid improve the growth responses, nutrient uptake, and essential oil content on Coriandrum sativum L.

Abstract: In recent decades, the over-use of chemical fertilizers has imposed many environmental challenges worldwide. Nowadays, organic fertilizers such as vermicompost and livestock manure have gained a huge interest in sustainable agricultural systems. A 2-year field research was conducted as factorial based on a randomized complete block design to assay the fertilizer and humic acid (HA) efficiency on the growth responses and essential oil composition of Coriandrum sativum. The treatments were different fertilizer s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 49 publications
1
6
0
2
Order By: Relevance
“…Özyazici, 2021 [ 86 ] identified different fertilizer sources that also affected the EO content from 0.29 to 0.33% in the Erbaa variety of coriander. The same observation was given by Rasouli et al [ 87 ] where the different fertilizer type affected the EO content from 30–37% when compared to the control.…”
Section: Variation In Eo Due To Other Factorssupporting
confidence: 83%
“…Özyazici, 2021 [ 86 ] identified different fertilizer sources that also affected the EO content from 0.29 to 0.33% in the Erbaa variety of coriander. The same observation was given by Rasouli et al [ 87 ] where the different fertilizer type affected the EO content from 30–37% when compared to the control.…”
Section: Variation In Eo Due To Other Factorssupporting
confidence: 83%
“…[ 30 ] stated that the application of HA on the growth and yield parameters of field-grown basil plants was effective, and they observed the best growth and yield with the highest HAD. A field study conducted with coriander reported increased plant growth, plant height, biological yield, and grain yield with the application of HA [ 48 ]. Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have confirmed the beneficial effects of HA and FA on plant yielding [35], nutrient metabolism, and the synthesis of compounds involved in plant adaptation to stress factors [28,33,36]. What is more, humic substances promote seed germination and seedling development [37,38] and root growth [39,40] and increase the cell membrane permeability and stimulate the synthesis of nucleotides [41], chlorophyll [42], proteins, and monosaccharides [35]. Thanks to its ability to bind and precipitate harmful substances, soil humus also serves a protective function in the environment [43] and affects the behaviour and availability of trace elements in the soil [44].…”
Section: Introductionmentioning
confidence: 99%